Notes on the Developmental Pattern of Leg Paralysis Induced by Risella 17 oil on Lucilia sericata (Meigen) - Lim, G. S. (1980)
The developmental pattern of leg paralysis in Lucilia sericata (Meig.) induced by 0.3 pi Risella 17 oil (applied topically) was observed to differ according to whether the appendages belong to the fore-, mid-, or hindlegs. In general the forelegs were least susceptible and the number of paralytic legs increased with time. By 3 days after treatment most of the affected flies had 3-4 legs paralysed. Also evident is a strong association between the type of paralytic symptoms and the kind ofappendages.